Flow-based In Vivo Method to Enumerate Translating Ribosomes and Translation Elongation Rate - Mina Seedhom; Devin Dersh; Jonathan Yewdell (Bio-Protocol)
Protein synthesis is by far the most energetically costly cellular process in rapidly dividing cells. Quantifying translating ribosomes in individual cells and their average mRNA transit rate is arduous. Quantitating assembled ribosomes in individual cells requires electron microscopy and does not indicate ribosome translation status. Measurement of average transit rates entails in vitro pulse-chase radiolabeling of isolated cells or ribosome profiling after ribosome runoff, which is expensive and extremely demanding technically. Here, we detail protocols based on ribosome-mediated nascent chain puromycylation, harringtonine to stall initiating ribosomes while allowing ribosome elongation to continue normally, and cycloheximide to freeze translating ribosomes in place. Each compound is delivered intravenously to mice in the appropriate order, and after ex vivo cell fixation and permeabilization, translating ribosome numbers and transit rates are measured by flow cytometry using a directly conjugated puromycin-specific antibody.